2014
DOI: 10.1007/s11207-014-0615-6
|View full text |Cite
|
Sign up to set email alerts
|

Decameter U-burst Harmonic Pair from a High Loop

Abstract: The results of the first observations of solar sporadic radio emission within 10 -70 MHz by the Giant Ukrainian Radio Telescope (GURT) are presented and discussed. Observations in such a wide range of frequencies considerably facilitate the registration of harmonic pairs. The solar U-burst harmonic pair observed on 8 August 2012 is analyzed. The burst key features were determined. Among them, the time delay between the fundamental and harmonic emissions was of special interest. The fundamental emission was del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 18 publications
2
18
1
Order By: Relevance
“…Using a series of 29 U-bursts observed below 160 MHz Labrum & Stewart (1970) used the time associated with the width of the 'U' in the dynamic spectra at twice the turnover frequency and, together with a density model, estimated average velocities of 0.25 c. If the exciter velocity of U-bursts and J-bursts remains roughly constant then the curvature in the dynamic spectrum must correspond to a substantial decrease in the density gradient within the coronal loop, but this assumption has yet to be explored. Recently Dorovskyy et al (2015) used the time delay between the fundamental and harmonic components of a U-burst to deduce the temperature within a magnetic loop, dependent upon the velocity of the exciting electron beam.…”
Section: Introductionmentioning
confidence: 99%
“…Using a series of 29 U-bursts observed below 160 MHz Labrum & Stewart (1970) used the time associated with the width of the 'U' in the dynamic spectra at twice the turnover frequency and, together with a density model, estimated average velocities of 0.25 c. If the exciter velocity of U-bursts and J-bursts remains roughly constant then the curvature in the dynamic spectrum must correspond to a substantial decrease in the density gradient within the coronal loop, but this assumption has yet to be explored. Recently Dorovskyy et al (2015) used the time delay between the fundamental and harmonic components of a U-burst to deduce the temperature within a magnetic loop, dependent upon the velocity of the exciting electron beam.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the fact that the U-and J-bursts turnover points were unambiguously determined on the timefrequency plane it became possible to determine the real frequency ratio and the time delay between the components of a harmonic pair. Thus, on basis of joint observations with the radio telescopes UTR-2 and GURT (Ukraine) held on 8 August 2012 it was found that the turnover frequencies ratio in the harmonic pair was close to 2 [22] (Fig. 2(a)).…”
Section: U-and J-burstsmentioning
confidence: 82%
“…There are three possible factors that can lead to the delay between lower and higher harmonics (e.g. Dorovskyy et al, 2015;Kong et al, 2016). Firstly, the group speed of the lower harmonics is smaller than that of higher ones, so it takes a longer time for the lower harmonics to propagate to the Earth from the spike source as shown in Figure 6b.…”
Section: Causes Of Temporal Delay Of Lower Harmonicsmentioning
confidence: 99%